Submandibular gland sialolith in a renal transplant recipient: A case report - Lívia Soares (2005)
Salivary dysfunction may be due to systemic diseases and medications. The development of sialoliths is a multifactorial event in which disturbances in secretion, microliths, and bacteria may play a major role. A case of sialolith in the submandibular gland of a 58-year old woman, with a medical history of renal failure end kidney transplant, is reported.